Salivary gland epithelial cells from patients with Sjögren's syndrome induce B-lymphocyte survival and activation. Issue 11 (25th August 2020) - Rivière, Elodie; Pascaud, Juliette; Tchitchek, Nicolas; Boudaoud, Saida; Paoletti, Audrey; Ly, Bineta; Dupré, Anastasia; Chen, Hua; Thai, Alice; Allaire, Norm; Jagla, Bernd; Mingueneau, Michael; et al.
Abstract : Objective: Primary Sjögren's syndrome (pSS) is characterised by chronic hyperactivation of B lymphocytes. Salivary gland epithelial cells (SGECs) could play a role in promoting B-lymphocyte activation within the target tissue. We aimed to study the interactions between SGECs from patients with pSS or controls and B lymphocytes. Methods: Patients had pSS according to 2016 European League Against Rheumatism/American College of Rheumatology criteria. Gene expression analysis of SGECs and B lymphocytes from pSS and controls isolated from salivary gland biopsies and blood was performed by RNA-seq. SGECs from pSS and controls were cocultured with B-lymphocytes sorted from healthy donor blood and were stimulated. Transwell and inhibition experiments were performed. Results: Gene expression analysis of SGECs identified an upregulation of interferon signalling pathway and genes involved in immune responses ( HLA-DRA, IL-7 and B-cell activating factor receptor ) in pSS. Activation genes CD40 and CD48 were upregulated in salivary gland sorted B lymphocytes from patients with pSS. SGECs induced an increase in B-lymphocyte survival, which was higher for SGECs from patients with pSS than controls. Moreover, when stimulated with poly(I:C), SGECs from patients with pSS induced higher activation of B-lymphocytes than those from controls. This effect depended on soluble factors. Inhibition with anti-B-cell activating factor, anti-A proliferation-inducing ligand, anti-interleukin-6-R antibodies, JAK1/3 inhibitor or hydroxychloroquine had no effect, conversely to leflunomide, Bruton's tyrosine kinase (BTK) or phosphatidyl-inositol 3-kinase (PI3K) inhibitors. Conclusions: SGECs from patients with pSS had better ability than those from controls to induce survival and activation of B lymphocytes. Targeting a single cytokine did not inhibit this effect, whereas leflunomide, BTK or PI3K inhibitors partially decreased B-lymphocyte viability in this model. This gives indications for future therapeutic options in pSS.